Role of Lactobacillus reuteri in Human Health and Diseases - Mu, Qinghui; Tavella, Vincent J.; Luo, Xin M. (Frontiers in Microbiology, 2018)
Lactobacillus reuteri (L. reuteri) is a well-studied probiotic bacterium that can colonize a large number of mammals. In humans, L. reuteri is found in different body sites, including the gastrointestinal tract, urinary tract, skin and breast milk. The abundance of L. reuteri varies among different individuals. Several beneficial effects of L. reuteri have been noted. Firstly, L. reuteri can produce antimicrobial molecules, such as organic acids, ethanol and reuterin. Due to its antimicrobial activity, L. reuteri is able to inhibit the colonization of pathogenic microbes and remodel the commensal microbiota composition in the host. Secondly, L. reuteri can benefit the host immune system. For instance, some L. reuteri strains can reduce the production of pro-inflammatory cytokines while promoting regulatory T cell development and function. Thirdly, bearing the ability to strengthen the intestinal barrier, the colonization of L. reuteri may decrease the microbial translocation from the gut lumen to the tissues. Microbial translocation across the intestinal epithelium has been hypothesized as an initiator of inflammation. Therefore, inflammatory diseases, including those located in the gut as well as in remote tissues, may be ameliorated by increasing the colonization of L. reuteri. Notably, the decrease in the abundance of L. reuteri in humans in the past decades is correlated with an increase in the incidences of inflammatory diseases over the same period of time. Direct supplementation or prebiotic modulation of L. reuteri may be an attractive preventive and/or therapeutic avenue against inflammatory diseases.